Extent of the protection afforded by histo-blood group polymorphism against rotavirus gastroenteritis in metropolitan France and French Guiana - Masson, Lydie; Barbé, Laure; Henaff, Fanny; Ahmed, Tasnuva; Le Moullac-Vaidye, Béatrice; Peltier, Cécile; Marchand, Sarah S; Scherdel, Pauline; Vibet, Marie-Anne; Ruvoën-Clouet, Nathalie; Elenga, Narcisse; Imbert-Marcille, Berthe-Marie; et al. (Frontiers in Microbiology, 2023)
Human rotaviruses attach to histo-blood group antigens glycans and null alleles of the ABO, FUT2 and FUT3 genes seem to confer diminished risk of gastroenteritis. Yet, the true extent of this protection remains poorly quantified. Here, we conducted a prospective study to evaluate the risk of consulting at the hospital in non-vaccinated pediatric patients according to the ABO, FUT2 (secretor) and FUT3 (Lewis) polymorphisms, in Metropolitan France and French Guiana. At both locations, P genotypes were largely dominated by P[8]-3, with P[6] cases exclusively found in French Guiana. The FUT2 null (nonsecretor) and FUT3 null (Lewis negative) phenotypes conferred near full protection against severe gastroenteritis due to P[8]-3 strains (OR 0.03, 95% CI 0.00-0.21 and 0.1, 95% CI 0.01-0.43, respectively in Metropolitan France; OR 0.08, 95% CI 0.01-0.52 and 0.14, 95%CI 0.01-0.99, respectively in French Guiana). Blood group O also appeared protective in Metropolitan France (OR 0.38, 95% CI 0.23-0.62), but not in French Guiana. The discrepancy between the two locations was explained by a recruitment at the hospital of less severe cases in French Guiana than in Metropolitan France. Considering the frequencies of the null ABO, Secretor and Lewis phenotypes, the data indicate that in a Western European population, 34% (95% CI [29 %; 39%]) of infants are genetically protected against rotavirus gastroenteritis of sufficient severity to lead to hospital visit.